2017
DOI: 10.1002/ccr3.1094
|View full text |Cite
|
Sign up to set email alerts
|

Primary cardiac lymphoma with central nervous system relapse

Abstract: Key Clinical MessagePrimary cardiac lymphoma (PCL), a rare disease, often presents with symptoms resembling other cardiac diseases. The correct diagnosis is crucial, as cardiac lymphoma can be cured with immuno‐chemotherapy. PCL has a high risk of central nervous system recurrence (CNS); therefore, screening for CNS involvement and even prophylaxis may be necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Secondly, cardiovascular comorbidities are not included in the SEER database, and we were unable to further explore the impact of cardiovascular comorbidities on CVD in PCNSL patients. Recent study by Michael Brendan Cloney et al (43) found that cardiac risk predicted systemic complications among patients with PCNSL, and the PCNSL patients with resection had higher cardiac risk, but it is still unclear whether this risk is related to surgical resection or disease itself. A case report of Cleo R van Rooijen et al (44) found that primary cardiac lymphoma had a high risk of central nervous system recurrence, suggesting that cardiovascular system (e.g., heart, etc) may be potentially affected in PCNSL patients, which may cause various cardiovascular abnormalities and poor prognosis.…”
Section: Study Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, cardiovascular comorbidities are not included in the SEER database, and we were unable to further explore the impact of cardiovascular comorbidities on CVD in PCNSL patients. Recent study by Michael Brendan Cloney et al (43) found that cardiac risk predicted systemic complications among patients with PCNSL, and the PCNSL patients with resection had higher cardiac risk, but it is still unclear whether this risk is related to surgical resection or disease itself. A case report of Cleo R van Rooijen et al (44) found that primary cardiac lymphoma had a high risk of central nervous system recurrence, suggesting that cardiovascular system (e.g., heart, etc) may be potentially affected in PCNSL patients, which may cause various cardiovascular abnormalities and poor prognosis.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Recent study by Michael Brendan Cloney et al. ( 43 ) found that cardiac risk predicted systemic complications among patients with PCNSL, and the PCNSL patients with resection had higher cardiac risk, but it is still unclear whether this risk is related to surgical resection or disease itself. A case report of Cleo R van Rooijen et al.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Although it is mostly seen with cardiac symptoms, it can also occur asymptomatically. Generally, clinical manifestation occurs with right ventricular dysfunction and tamponade, which also carry important clues for central nervous system involvement [16].…”
Section: Discussionmentioning
confidence: 99%
“…Prophylaxis with intrathecal chemotherapy has resulted in varied outcomes 31,32. It is currently unknown the efficacy of CNS prophylaxis at CNS relapse, and the debate on the optimal route of CNS prophylaxis (intrathecal versus systemic) is still ongoing 14. Patient’s status may be the most critical factor for therapeutic efficacy, which should be accurately evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…In order to improve the diagnostic efficacy, there is emerging interest in finding new biomarkers, such as circulating tumor cells (CTC), proteins, as well as micro-RNA and DNA 7,12,13. CNS disease typically developed within a few months before the initial clinical presentation, raising the question: whether occult CNS localization was already present at the time of diagnosis 14. The BBB and the blood-cerebrospinal- fluid barrier (BCSFB) are the effective barriers to inhibit large molecules and cells into the CNS.…”
Section: Introductionmentioning
confidence: 99%